Short-term outcomes with the REDAPT monolithic, tapered, fluted, grit-blasted, forged titanium revision femoral stem. (February 2020) - Gabor, Jonathan A.; Padilla, Jorge A.; Feng, James E.; Schnaser, Erik; Lutes, William B.; Park, Kwan J.; Incavo, Stephen; Vigdorchik, Jonathan; Schwarzkopf, Ran
Abstract : Aims: Although good clinical outcomes have been reported for monolithic tapered, fluted, titanium stems (TFTS), early results showed high rates of subsidence. Advances in stem design may mitigate these concerns. This study reports on the use of a current monolithic TFTS for a variety of indications. Methods: A multi-institutional retrospective study of all consecutive total hip arthroplasty (THA) and revision total hip arthroplasty (rTHA) patients who received the monolithic TFTS was conducted. Surgery was performed by eight fellowship-trained arthroplasty surgeons at four institutions. A total of 157 hips in 153 patients at a mean follow-up of 11.6 months (SD7.8) were included. Mean patient age at the time of surgery was 67.4 years (SD 13.3) and mean body mass index (BMI) was 28.9 kg/m 2 (SD 6.5). Outcomes included intraoperative complications, one-year all-cause re-revisions, and subsidence at postoperative time intervals (two weeks, six weeks, six months, nine months, and one year). Results: There were eight intraoperative complications (4.9%), six of which were intraoperative fractures; none occurred during stem insertion. Six hips (3.7%) underwent re-revision within one year; only one procedure involved removal of the prosthesis due to infection. Mean total subsidence at latest follow-up was 1.64 mm (SD 2.47). Overall, 17 of 144 stems (11.8%) on which measurements could be performed had >5 mm of subsidence, and 3/144 (2.1%) had >10 mm of subsidence within one year. A univariate regression analysis found that additional subsidence after three months was minimal. A multivariate regression analysis found that subsidence was not significantly associated with periprosthetic fracture as an indication for surgery, the presence of an extended trochanteric osteotomy (ETO), Paprosky classification of femoral bone loss, stem length, or type of procedure performed (i.e. full revision vs conversion/primary). Conclusion: Advances in implant design, improved trials, a range of stem lengths and diameters, and high offset options mitigate concerns of early subsidence and dislocation with monolithic TFTS, making them a valuable option for femoral revision. Cite this article: Bone Joint J 2020;102-B(2):191–197.